I11 Respiratory Function Decreases With Progression Of Huntington's Disease. (17th September 2014) - Jones, U; Busse, M; Enright, S; Rosser, A
Abstract : Background: There is some evidence of altered central respiratory rhythm and upper airway obstruction in people with Huntington's disease (HD) (Antczak et al . 2013) yet little known of the consequences of HD pathology on respiratory function. Aims: In order to inform our knowledge of respiratory problems in people with HD, this study assessed respiratory function across the progression of the disease and compared it to healthy control participants. Methods: Data from 67 people with HD (20 pre-manifest) and 39 healthy control participants were evaluated for differences. Respiratory function was assessed as lung volume, peak cough flow, and respiratory muscle strength. Data were analysed using Kruskall-Wallis and Mann-Whitney-U for post hoc comparisons; correlations were used to explore respiratory function and disease progression. Flow volume curves were analysed descriptively. Results: Respiratory function was significantly decreased in people with manifest HD compared to healthy control participants (inspiratory muscle strength mean difference 57.4 cm H2 O, CI 45.97, 68.84) and people with pre-manifest HD (inspiratory muscle strength mean difference 61.4 cm H2 O, CI 48.23, 74.58), with no differences between healthy control participants and people with pre-manifest HD. Respiratory function declined linearly with disease progression measured by total functional capacity scale (p < 0.001), in particular, peak cough flow was abnormal at the middle stage of the disease. Flow volume curves indicated upper airway resistance to flow. Conclusion: This study confirms that respiratory function is different in HD compared with healthy controls and that respiratory function decreases linearly with disease progression. These findings have implications for monitoring and managing respiratory problems throughout HD disease progression with decreased lung volume and peak cough flow increasing the likelihood of pneumonia. Reduced respiratory muscle strength may result in decreased exercise capacity whilst increased upper airways resistance may influence sleep apnoea. Further research is needed to explore the underlying cause of respiratory dysfunction in HD. Antczak J, et al . Huntington's Disease and Sleep Related Breathing Disorders. Hygeia 2013;48(4):pp. 449-455